Analisis Pengelolaan SDM Desa Tujuan Objek Wisata Melalui Community Based Tourism (CBT) Terhadap Kesejahteraan Masayarakat (Studi Empiris Pada Kelurahan Kandri, Kecamatan Gunungpati, Semarang) - Farya Arkham Maulana; Vina Putri Handayani; Farikhah Amaniyah; Fira Novita Nur Septiyanti; Ratih Pratiwi (Sekolah Tinggi Ilmu Ekonomi AMA Salatiga, 2022)
In developing a tourist village, it is necessary to contribute to the application of CBT, which is expected to improve the welfare of the tourism village community. This will continue with CBT-Based HR management as a form of direction for the government and society to develop superior products for tourist villages. In Semarang there are many tourist villages, one of which is Kandri tourism village, this tourist village has won various awards, in which the development of this tourist village requires support from various layers of existing human resources as well as the role of government and community in terms of human resource management. Therefore, this study aims to determine how influential the management of human resources through CBT is on the welfare of the community. This study uses a qualitative descriptive method with a data collection technique through observation, interviews, and documentation as well as a purposive sampling technique. The results of this study indicate that there is a significant relationship between human resource management and the application of CBT to the welfare of the community in the Kandri tourist village, the cohesiveness of community collaboration inside and outside the Kandri village can create welfare for the community so as to produce productive and independent human resources.